Evolution characteristics of extreme maximum temperature events in Central China and adaptation strategies under different future warming scenarios - Duan Yiping; You Xia; Wang Rongrong; Ouyang Ping; Wang Guanhua; Chen Muyan; Gong Min (Open Geosciences)
This study examined the spatiotemporal characteristics of extreme maximum temperature events (EMTEs) in Central China using observational data from national meteorological stations and data from coupled model intercomparison project phase 6 models and by focusing on the variances between global warming thresholds of 1.5, 2.0, and 4°C. The extreme maximum temperature threshold was determined based on the 99th percentile of daily maximum temperature, and an improved intensity–area–duration method was employed to determine EMTE characteristics. Results indicated that during the reference period (1995–2014), the intensity, coverage, duration, and number of hot days of EMTEs in Central China increased by 0.19°C/10a, 1.6 × 105 km2/10a, 0.2 days/10a, and 3 days/10a, respectively. Compared with the reference period, under future scenarios of shared socioeconomic pathways SSP1-2.6, SSP2-4.5, SSP3-7.0, SSP4-6.0, and SSP5-8.5, the intensity, coverage, duration, and number of hot days of EMTEs increased by 0.05–0.21°C/10a, 0.54–4.3 × 105 km2/10a, 0.12–1.19 days/10a, and 0.7–2.2 days/10a, respectively. Regionally, projected high values of intensity, duration, and number of hot days of EMTEs were mainly concentrated in eastern Henan, northeastern Hubei, eastern Hubei, eastern Jiangxi, and central regions. For warming of 1.5, 2.0, and 4.0°C, the larger the warming threshold, the greater the likelihood of EMTEs. Considering the increasing probability of more severe EMTEs, it is recommended that research on the monitoring, early warning, and forecasting of EMTEs be strengthened, and that effective measures be taken to limit the increase in global temperature to within 1.5°C to mitigate the impacts of such events.